Splenogonadal fusion in an 18-month-old. Issue 2 (April 2017) - Preece, J.; Phillips, S.; Sorokin, V.; Herz, D.
Summary: Background: Splenogonadal fusion is rare abnormal congenital connection of splenic tissue and gonad. It commonly presents with either cryptorchidism or as a palpable mass. As a benign anomaly, orchiectomy is often unnecessary. Removal of the splenic component may be accomplished with preservation of the testicle. Methods: An 18-month-old boy presented with right cryptorchidism and left retractile testicle. Laparoscopic examination found a viable right testicle, and a successful orchiopexy was performed. The left testicle demonstrated splenogonadal fusion. Discontinuous accessory splenules were noted along the path of testicular descent. After confirmation from a radionucleotide liver-spleen scan the patient was brought back to the operating room for open excision of the adherent splenic tissue and orchiopexy of the testicle via an open inguinal approach. Conclusion: Splenogonadal fusion is a rare condition, but may be suspected in children with cryptorchidism or palpable peri-testicular mass. As with the present patient, in most cases the splenic tissue may be successfully excised without injury to the testicle.